Almost periodic synchronization of fuzzy cellular neural networks with time-varying delays via state-feedback and impulsive control - Li, Yongkun; Wang, Huimei; Meng, Xiaofang (Zielona Góra: Uniwersytet Zielonogórski)
In this paper, we are concerned with drive-response synchronization for a class of fuzzy cellular neural networks with time varying delays. Based on the exponential dichotomy of linear differential equations, the Banach fixed point theorem and the differential inequality technique, we obtain the existence of almost periodic solutions of this class of networks. Then, we design a state feedback and an impulsive controller, and construct a suitable Lyapunov function to study the problem of global exponential almost periodic synchronization for the drive-response systems considered. At the end of the paper, we provide an example to verify the effectiveness of the theoretical results
Keywords: almost periodic solution; fuzzy cellular neural networks; time-varying delays; synchronization; state feedback; impulsive control